2011
DOI: 10.1016/j.pmrj.2011.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Telerehabilitation: Applications for Physiatrists

Abstract: Telemedicine offers an innovative approach to increase access to rehabilitation medicine services for patients who live in areas where physiatrists are scarce or absent. This article reviews the current status of telerehabilitation services delivered through real-time videoconferencing to provide support, assessment, and interventions to individuals with impairments or disabilities. A literature review demonstrates various uses of telerehabilitation by physical therapists, occupational therapists, speech and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 66 publications
1
47
0
4
Order By: Relevance
“…Despite a lack of trials in this area (Laver et al, 2013), e‐health technology seems promising and is increasingly used (Gregory et al, 2011; White et al, 2014). The functionality and content of the current app and telerehabilitation services in C4S can be expanded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a lack of trials in this area (Laver et al, 2013), e‐health technology seems promising and is increasingly used (Gregory et al, 2011; White et al, 2014). The functionality and content of the current app and telerehabilitation services in C4S can be expanded.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that this app can support adherence to the programme by patient and caregiver and promote self‐management (Gregory, Alexander, & Satinsky, 2011; White, Janssen, Jordan, & Pollack, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Most of these programs have focused on rehabilitation of physical disability or speech impairment 5,9,13,14,17,18) . In contrast, only a few studies have reported on telerehabilitation for cognition 7,8,10) .…”
Section: Discussionmentioning
confidence: 99%
“…These studies have been performed using internet-based virtual reality or computer software programs. With the rapid spread of tablet PCs and smartphones, many applications have been developed for rehabilitation 11,13,15,16,19,20) . Some studies have demonstrated the usefulness of smartphones for improvement of memory impairment [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation